2007
DOI: 10.1007/s11894-007-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

Dyspepsia in childhood and adolescence: Insights and treatment considerations

Abstract: Functional dyspepsia (FD) is common in children, with as many as 80% of those being evaluated for chronic abdominal pain reporting symptoms of epigastric discomfort, nausea, or fullness. It is known that patients with persistent complaints have increased comorbidities such as depression and anxiety. The interaction with psychopathologic variables has been found to mediate the association between upper abdominal pain and gastric hypersensitivity. These observations suggest that abnormal central nervous system p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 77 publications
(65 reference statements)
0
17
0
1
Order By: Relevance
“…[38] The pain or discomfort can be associated with vomiting, nausea, abdominal fullness, bloating or early satiety. [39] Hyams and colleagues [40] reported that 26% of 127 pediatric subjects had ulcer-like symptoms while 15% manifested dysmotility-like symptoms.…”
Section: Functional Dyspepsiamentioning
confidence: 99%
“…[38] The pain or discomfort can be associated with vomiting, nausea, abdominal fullness, bloating or early satiety. [39] Hyams and colleagues [40] reported that 26% of 127 pediatric subjects had ulcer-like symptoms while 15% manifested dysmotility-like symptoms.…”
Section: Functional Dyspepsiamentioning
confidence: 99%
“…Because the mechanism of chronic idiopathic nausea is not understood, treatments have been empirical and less effective than desired [1]. Electrogastrography has been used to determine if symptoms such as nausea and vomiting are associated with abnormal gastric rhythms that disrupt normal gastric peristalsis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased gastric accommodation is associated with symptoms including early satiety, bloating, epigastric pain, weight loss and nausea. 5 Delayed gastric emptying, altered antroduodenal motility, and impaired gastric accommodation have been proposed to explain symptoms of functional dyspepsia. [5][6][7][8][9] However, despite of the higher incidence of delayed gastric emptying and decreased gastric motility in the group of children with gastroptosis, there was no difference in the presence of GI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Delayed gastric emptying, altered antroduodenal motility, and impaired gastric accommodation have been proposed to explain symptoms of functional dyspepsia. [5][6][7][8][9] It is not known if gastroptosis itself leads to certain symptoms or if gastroptosis and related symptoms are the result of another disease. Symptoms related to gastroptosis are nonspecific and could be caused by many other conditions.…”
Section: Introductionmentioning
confidence: 99%